Vitamin E and selenium supplementation to alleviate cold-stress-associated deterioration in egg quality and egg yolk mineral concentrations of Japanese quails - Şahin, Nurhan; Şahin, Kazım; Onderci, M (Springernature, 2003)
The effects of vitamin E (dl-alpha-tocopheryl acetate) and selenium (Se; Na-2-SeO3) on egg production, egg quality, and mineral content of egg yolk in Japanese quails reared under a low ambient temperature (6degreesC) were evaluated. Birds (n = 300; 7 wk old) were randomly assigned to 12 treatment groups, 25 birds per group. The birds in a 3x2 factorial design received either three levels of vitamin E (125, 250, and 500 mg/kg diet) or two levels of selenium (0.1 or 0.2 mg/kg diet). After 2 wk on feed, six groups of the birds were maintained at 18degreesC (thermoneutral temperature [TN]), and the other half were acclimated over 3 d to a decreased environmental temperature of 6degreesC (cold stress [CS]). The performance, egg quality, and mineral content of egg yolk were not influenced by supplemental vitamin E and selenium in quails not exposed to cold stress (p greater than or equal to 0.09). Two hundred fifty and 500 mg vitamin E/kg diet compared with 125 mg/kg diet and higher dietary selenium inclusions (0.2 vs 0.1 mg/kg) resulted in a better body weight, egg production, and feed efficiency (p = 0.01) in quails reared under CS. Similarly, egg weight, egg specific gravity, eggshell thickness, and Haugh unit were positively influenced with vitamin E (p = 0.01) and selenium (p less than or equal to 0.05) supplementation. Egg yolk concentrations of Zn, Fe, and Mn were higher with higher dietary vitamin E (p = 0.01) and selenium (p = 0.05). There was no interaction detected for parameters measured in the present study (p greater than or equal to 0.3). The results of the present study showed that a combination of 250 or 500 mg vitamin E and 0.2 mg selenium per kilogram of diet provides the greatest effects on performance and egg quality of Japanese quails reared under cold stress and suggest that such a supplementation can be considered as a protective management practice in Japanese quail diets to reduce the detrimental effects of cold stress.
Keywords: Laying Hens; Lipid-Peroxidation; Antioxidant Status; Dietary Chromium; Heat-Stress; Performance; Temperature; Metabolites; Nutrients; Responses